Uji Antimikroba Curcuma spp. Terhadap Pertumbuhan Candida albicans, Staphylococcus aureus dan Escherichia coli - Rahmi Adila; - Nurmiati; Anthoni Agustien (Universitas Andalas, 2013)
A study about the effect of fresh extract of Curcuma spp on the growth of Candida albicans, Staphylococcus aureus and Escherichia coli was conducted from March to July 2012 at Microbiology Laboratory, Faculty of Sciences Andalas University. This experiment used nested completely randommized design. The result showed that fresh extracts of Curcuma spp. have different growth inhibition effects on C. albicans, S. aureus dan E. Coli. Temulawak (Curcuma xhantorrhiza) has the highest inhibition effect to the growth of C. albicans (13.07 mm), S. aureus (15.75 mm) and E. coli (31.56 mm). The lowest bactericidal consentration of fresh extract rhizome of temulawak for E. coli were 12.5% and 25%, but there is no inhibition effect to the C. albicans and S. aureus.Keywords: Curcuma, antimicrobial, extract, pathogen microbial